2016
DOI: 10.2337/db16-0416
|View full text |Cite
|
Sign up to set email alerts
|

The Inactivation of RabGAP Function of AS160 Promotes Lysosomal Degradation of GLUT4 and Causes Postprandial Hyperglycemia and Hyperinsulinemia

Abstract: The AS160 (Akt substrate of 160 kDa) is a Rab-GTPase activating protein (RabGAP) with several other functional domains, and its deficiency in mice or human patients lowers GLUT4 protein levels and causes severe insulin resistance. How its deficiency causes diminished GLUT4 proteins remains unknown. We found that the deletion of AS160 decreased GLUT4 levels in a cell/ tissue-autonomous manner. Consequently, skeletal muscle-specific deletion of AS160 caused postprandial hyperglycemia and hyperinsulinemia. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…Insulin-stimulated GLUT4 translocation onto plasma membrane was impaired in the AS160 Thr649Ala knockin mice although expression of the transporter was elevated [25]. In contrast, expression of GLUT4 was decreased in various muscles and adipose tissue of the AS160 deficient mouse models [38][39][40] as well as in skeletal muscles from human patients who harbor a pre-mature stop codon Arg 684 Ter on AS160 [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-stimulated GLUT4 translocation onto plasma membrane was impaired in the AS160 Thr649Ala knockin mice although expression of the transporter was elevated [25]. In contrast, expression of GLUT4 was decreased in various muscles and adipose tissue of the AS160 deficient mouse models [38][39][40] as well as in skeletal muscles from human patients who harbor a pre-mature stop codon Arg 684 Ter on AS160 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the reduced GLUT4 levels in one of the TBC1D1 knockout mouse models caused a decrease in exercisestimulated glucose uptake in nonoxidative muscle fibers and consequently impaired exercise endurance [44]. It has been recently shown that the loss of AS160 GAP activity accelerates lysosomal degradation of GLUT4 [40]. A key question remaining to be answered in all the TBC1D1 mouse models is whether the effects on GLUT4 translocation or expression are dependent on the GAP activity of TBC1D1.…”
Section: Discussionmentioning
confidence: 99%
“…Published research in humans has not addressed the possibility that AS160 deficiency might not have identical consequences on males versus females [6]. Several studies using AS160-KO mice reported data only [4,7] or mostly [8] in males. Other studies reported data for both male and female AS160-KO mice for some, but not all outcomes [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we did not observe any alterations in muscle properties in muscle-specific Egr-1 knockout mice, which suggests that a deficiency in Egr-1 alone may not affect muscle morphology and performance. Skeletal muscle, a highly metabolically active tissue, has substantial insulin sensitivity, which results in glucose transport and glycogen breakdown during exercise (35)(36)(37); however, mechanistic studies have demonstrated that acute exercise does not increase phosphorylation of the PI3K/AKT pathway (38,39), but instead activates the phosphorylation of aPKC/AS160 (40,41). Thus, it is likely that the insulin-stimulated activation of PI3K/AKT by Egr-1 deletion does not affect glucose uptake or glycogen breakdown during exercise, thus explaining why the deletion of Egr-1 does not affect running ability or blood lactate levels.…”
Section: Discussionmentioning
confidence: 99%